EVOLUTION OF EXEMPTIONS TO CARRIER IN DIFFERENT MARITIME LEGAL REGIME - Talha, Ahmad (The journal of contemporary issues in business and government, 2022)
Trade is done all over the world in different ways. From history till now, it has evolved from time to time. As technology becomes more sophisticated, different issues, either legal or ethical, also emerge. The main elements of a successful trade are always trust and expeditious service. It has long been established that sea trade is more vital and cost-effective than other modes of transportation, whether by road, rail, or air.This means the cargo owner and the carrier are also at odds over who is responsible for damage to the goods.At the outset of this international legal regime, which is comprised of the Hague and Hague-Visby Rules, there were a number of opportunities for carriers, including exemption from damage of goods, as well as a number of loopholes regarding jurisdiction and other exclusive provisions. Of these flaws, they make the carrier stronger and the cargo owner's position weaker. To establish a balance between cargo owner and carrier, UNCITRAL tries to introduce different rules from time to time, which is also questionable. But in the end, the Rotterdam Rule is one such instrument that provides uniformity in the rules of carriage of goods. This study compares different legal regimes which elaborate on how exemption of a carrier narrows down and how to establish a balance between carrier and cargo owner. In reality, carriers and ship-owners are one of the big and powerful industries that create different hurdles for ratification of the Rotterdam Rules and try to make Hague and Hague-Visby Rule applicability exist because they get a lot of benefit from it. This study focuses on different areas and provisions that are beneficial for carriers, and all states should come under one umbrella to ratify the Rotterdam Rules for a prosperous future and a uniform way for multimodal transportation.